FACTORS AFFECTING IMPLEMENTATION AND MAINTENANCE OF FALL WILD TURKEY SEASONS - Dale L. Garner; Steven D. Roberts (Wildlife Society Bulletin)
Abstract: Although wild turkeys (Meleagris gallopavo) were traditionally hunted in the fall, most states are currently placing a greater emphasis on spring hunting. With the emphasis shifting towards quality spring hunting, concerns exist regarding the effect of fall either‐sex harvest on the harvest of males in spring. We discuss factors influencing the implementation and maintenance of fall wild turkey seasons when the primary harvest management goal is to provide quality spring hunting opportunity. Fall harvest strategies consist of varying combinations of hunter quotas, season length, season timing, bag limits, and weapon type. Determining the maximum allowable fall harvest is difficult because reliable methods for estimating turkey populations are virtually nonexistent, and establishing the maximum allowable harvest at or below the 10% level is impossible without a population estimate. To ensure a stationary or increasing turkey population, the best approach in the absence of reliable population data is to establish conservative fall harvest levels and carefully monitor future harvest statistics and population indices. We believe that any established turkey population can endure a fall hunting season, however, severe restrictions may be required to satisfy spring harvest management goals. Given the dramatic growth of wild turkey populations over the past 30 years, the implementation and maintenance of limited fall turkey hunting seasons may be necessary to restrict future population growth.